The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0301-80591999000400011
|View full text |Cite
|
Sign up to set email alerts
|

Localização e aceitação de dieta artificial contendo feromônio sexual pelo predador Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae)

Abstract: -A mass rearing program of Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) is under development at the Federal University of Viçosa, MG, Brazil, aiming to release this predaceous insect for the control of caterpillars in Eucalyptus reforestation areas. As the location and acceptance of the artificial diet by P. nigrispinus needs to be improved, we tested the effect of the addition of its synthetic sex pheromone to the diet. We impregnated diets, inside and/or outside, with the complete pheromone blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Research has been conducted on diet components improving predator performance including the manner of offering the diet to the predators, additives to enhance location and acceptance of the artificial 'worms' (i.e. artificial diet enveloped by parafilm) by nymphs [107][108][109]. Brushing the outside of the parafilm 'skin' of the artificial worms with a dorso-abdominal gland crude extract [107] as well as with synthetic pheromone [109] reduced the time for diet location and feeding on the artificial worms by P. nigrispinus nymphs.…”
Section: Quantitative Mass Productionmentioning
confidence: 99%
“…Research has been conducted on diet components improving predator performance including the manner of offering the diet to the predators, additives to enhance location and acceptance of the artificial 'worms' (i.e. artificial diet enveloped by parafilm) by nymphs [107][108][109]. Brushing the outside of the parafilm 'skin' of the artificial worms with a dorso-abdominal gland crude extract [107] as well as with synthetic pheromone [109] reduced the time for diet location and feeding on the artificial worms by P. nigrispinus nymphs.…”
Section: Quantitative Mass Productionmentioning
confidence: 99%
“…Release of these predators against insect pests makes it necessary to study their biology and mass rearing so as to produce the highest possible number of individuals (Zanuncio et al, 2001). For this reason, these natural enemies have been reared with alternative preys such as Tenebrio molitor L., 1758 (Coleoptera: Tenebrionidae), Musca domestica L., 1758 (Diptera: Muscidae), or Bombyx mori L., 1758 (Lepidoptera: Bombycidae) (Beserra et al, 1995;Zanuncio et al, 1996Zanuncio et al, /1997Molina-Rugama et al, 1997;Nascimento et al, 1997;Jusselino Filho et al, 2001), in addition to artificial diets (Zanuncio et al, 1996;Saavedra et al, 1997;Coracini et al, 1999;De Clercq et al, 1998;and Rojas et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…From these works, studies on this subject have shown the attack strategy of Asopinae predators on pests, defense mechanisms of herbivores in predation conditions and acceptance of food in the form of natural or alternative prey or artificial diets (CARVALHO et al, 1995;CORACINI et al, 1999;FERREIRA et al, 2008;GROSMAN et al, 2005;LEMOS et al, 2005d;PIRES et al, 2009b;SAAVEDRA et al, 1997;SILVA et al, 2012;SOARES et al, 2009;VIVIAN et al, 2002). This helped to understand the occurrence of cannibalism in mass rearing and reduced losses caused by this behavior (PIRES et al, 2010a).…”
Section: Scientific Contributions In the Field Of Investigating Behavmentioning
confidence: 99%
“…In 1995, at the Federal University of Viçosa (UFV), the first doctoral thesis was defended which dealt specifically with Asopinae predators whose theme was "Artificial diet for Podisus nigrispinus (Dallas) and influence on its ability for predation of Anticarsia gemmatalis Hubner" (SAAVEDRA, 1995). Through years of research and investigations, advances with Asopinae predators have resulted in various studies of biology and plant health such as: increasing the number of species reported (THOMAS, 1992), definition and presentation of the main species for biological control programs (PIRES et al, 2009a;THOMAS, 1992), increase in the number of institutions collaborating in this line of research (Federal University of Viçosa -UFV, Federal University of Lavras -UFLA, Federal University of Mato Grosso -UFMT, Federal University of Vales do Jequitinhonha and Mucuri -UFVJM, Federal University of Paraíba -UFPB, Federal University of Grande Dourados -UFGD, Federal University of Rio Grande do Sul -UFRGS, Federal University of Minas Gerais -UFMG, Federal University of Pará -UFPA, Federal Rural Univeristy of Pernambuco -UFRPE and EMBRAPA), evolution of equipment for mass rearing and techniques and form of management (MOLINA-RUGAMA et al, 1998;PELÚZIO, 2012;PIRES et al, 2006;ZANUNCIO et al, 1994a), accommodation and ambience (MEDEIROS et al, 2003;SANTOS et al, 2005), physiology and internal and external morphology (AZEVEDO et al, 2007;GUEDES et al, 2007;LEMOS et al, 2006;2005a;SOARES et al, 2011;SÁ et al, 2013), studies on sensory and (ALDRICH et al, 1997;CORACINI et al, 1999;TORRES et al, 1997a) behavioral aspects (CARVALHO et al, 1995;1994;FERREIRA et al, 2008;LEMOS et al, 2005d;PIRES et al, 2010a;SAAVEDRA et al, 1997;SILVA et al, 2012;VIVIAN et al, 2002), toxicology, with focus on studies on selectivity of insecticides ...…”
Section: Introductionmentioning
confidence: 99%